(untitled) (Journal of Science and Technology, 2016)
Deep weathering conditions in tropical terrains often lead to a general scarcity of outcrops of relatively fresh rocks which would otherwise provide sources of good quality materials for road surfacing. As such, road construction becomes an expensive venture since suitable construction materials may sometimes have to be hauled over long distances at high cost. Road projects within the Sefwi Wiawso District, a typical tropical environment in Ghana, are often fraught with problems of procuring suitable crushed rocks, a situation which has recently necessitated research into the crushed rock potential of the district. An investigation, involving desk study of the geoenvironmental setting of the district, conduct of field studies and performance of relevant laboratory tests, was undertaken to evolve strategies for obtaining suitable crushed rock materials procured from two potential sources provided the requisite engineering properties for their utilisation in road surfacing because materials from no one source fully satisfied all the engineering geological requirements. This integrated approach can be readily employed for the effective evaluation of rock aggregates for road surfacing in similar geoenvironmental situations and elsewhere.